Flesh and blood - Painter, Kristen L. (Painter, Kristen L. House of Comarré, 2011)
When she discovers that she has a brother, Chrysabelle is torn between fulfilling a debt that means returning to Corbinestri, a hidden vampire city, with Malkolm, and family duty, while dealing with power hungry witches and the Kabai Mata.